Impact of wastewater-irrigated urban agriculture on diarrhea incidence in Ahmedabad, India - Timo Falkenberg; Deepak Saxena (Wolters Kluwer Medknow Publications, 2018)
Background: Urbanization and water scarcity are placing pressure on urban food security. Globally, wastewater irrigation is a common feature of urban agriculture; however, high pathogen densities of wastewater pose disease risk for farming households. Objectives: (a) Compare Escherichia coli concentrations of groundwater, surface, and wastewater. (b) Estimate the household diarrheal disease risk between the irrigation sources. Materials and Methods: This 12-month case-cohort study was undertaken in 187 households from four communities, selected purposively based on the irrigation water type, in urban Ahmedabad. The study included two communities utilizing surface water and one each using groundwater and wastewater. Households were visited bimonthly during each visit self-report health information was collected by health diary method. Water samples were analyzed for E. coli using the most probable number method. Results: Average E. coli concentrations, per 100 mL, in all the three water sources, were exceeding the international irrigation water standard and measured 3.04 × 104, 9.28 × 105, and 4.02 × 109 for groundwater, surface, and wastewater, respectively. The incidence of diarrhea in the groundwater area was 7.92 episodes/1,000 person-weeks, while the wastewater and surface water group had incidences of 13.1 and 13.4 episodes/1,000 person-weeks. A positive correlation between irrigation water quality and incidence of diarrhea was documented. The average treatment effect of wastewater quality obtained was 2.73. Conclusion: Large proportions of Ahmedabad's farming population rely on water unsuitable for irrigation, inducing significant adverse health effects for farming households. This warrants an urgent need of introducing the concept of urban agriculture to the local civic authorities.